Braking Pattern Impact on Brake Fade in an Automobile Brake System - Towoju O. A. (Журнал інженерних наук, 2019)
The importance of brake systems in automobiles cannot be overemphasized. Brakes are used in speed control of vehicles and do so by the conversion of kinetic energy into thermal energy. Better stopping performance has favored the disc brake system over the drum brake system and has found wide application in high-performance vehicles. Brake fade, caused by thermal overload has placed a limit on the permissible temperature at which braking systems can function, and it is the task of designers to ensure that this is avoided. However, even with a good design, panic braking at high speeds could lead to high-temperature values. This study is thus undertaken to numerically investigate the effect of selected braking patterns on temperature growth which could lead to brake fade in a disc brake system for a 2 200 kg car moving at a velocity of 40 m/s whose velocity is expected to be reduced to 4 m/s after five seconds with two matches of the brake for a seconds’ interval. The peak temperature attained in the system during braking was observed to be different for the different braking patterns, and the best-suited pattern was the 1s-1s-3s with peak temperature values below 600 K.